A Review of Aisha M. Beliso-De Jesús’s Excited Delirium: Race, Police Violence, and the Invention of a Disease - Andi Alfian (Elkuator Research and Publication, 2025)
In Excited Delirium: Race, Police Violence, and the Invention of a Disease, Aisha M. Beliso-De Jesús examines excited delirium, a pseudo-racialized medical diagnosis that has been used to explain the deaths of Black and Brown people in police custody. Beliso-De Jesús argues that excited delirium is used to legitimize police violence against people who are stigmatized as “the drug-addled, unhinged, superhuman Black persons.” Through this book, and this is the most important aspect for me in reading this book, Beliso-De Jesús shows that Afro-Latine religious traditions, especially the practices of copresences (taking spirits and spiritualism seriously), can serve not only to understand this racial violence, but also to heal.